Makna Lagu '33x' Karya Perunggu dalam Perspektif Teologis - Habibullah Habibullah; Dadan Firdaus; Tazkiyah Marwah Arina; Cita Afiyah Nursanti (INDO PUBLISHING, 2026)
Indonesian popular music, particularly within the indie genre, increasingly demonstrates thematic depth that transcends mere entertainment. This study examines the theological meanings embedded in the lyrics of